Arad and the 5 Stars Cities - Marian Gheorghe (Journal of Humanistic and Social Studies, 2019)
In 2000, Arad city was included in the 5 Stars Cities project, initiated by the US Embassy in Bucharest through USAID and IRIS, in partnership with the Romanian Government, a project of good administrative practices addressed to SMEs aimed at reducing bureaucracy, reducing the authorization procedures and terms for SME operation, streamlining the endorsement process, and building a base for business-to-business assets. A five-step process that once went to the first local government to complete its 5 Stars City title.